Mixed Reality (MR) dalam Pembelajaran Folklor dalam Perspektif Guru Dan Siswa Sekolah Dasar - Yunus Abidin; Tita Mulyati; Yeni Yuniarti; Tri Falah Nur Huda (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2021)
The development of the 21st century has had a major impact on developments in various aspects of life including economic, social, and educational aspects. In this regard, education in the 21st century is faced with a number of major challenges, one of which is to develop students who are technologically literate but also culturally literate. Thus, there is a need for a change to the pattern of learning in Indonesian education today that further develops high knowledge, understanding, and skills in line with 21st century technological advances but still ignores core cultural knowledge. In line with this, the first step in realizing this research is to design a mixed reality (MR)-based folklore learning media to develop students' learning abilities and cultural literacy. In line with this, the research aims to determine the perspectives of teachers and elementary school students in West Java on the use of mixed reality in folklore learning. This research was conducted using a descriptive method. The instruments used to collect data are observation guidelines, interview guidelines, and questionnaires. The data was processed using descriptive statistics. Based on the results of the study, it can be stated that the mixed reality media used in folklore learning in the view of teachers and students in elementary schools in West Java is able to motivate students to learn and the media developed is considered very good in quality, function, and benefits.